2018
DOI: 10.1111/jre.12595
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of para‐ and proinflammatory neutrophil phenotypes using transmission electron microscopy

Abstract: Oral neutrophils display morphological changes consistent with partial or full activation, corresponding to their para- or proinflammatory states. These changes can also be induced in naïve cells by incubating them with commensal bacteria. Neutrophils change their morphology towards an activated state as they travel through the gingival tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
(84 reference statements)
0
26
0
Order By: Relevance
“…It has been previously shown that not all neutrophils in the oral cavity display similar levels of cell surface CD marker expression (5,11,12). In the healthy oral cavity, neutrophils are in a parainflammatory state, whereas in a diseased cavity, neutrophil phenotypes are changed to a proinflammatory state, with neutrophils in the parain-flammatory and proinflammatory states expressing low levels and high levels of CD markers, respectively (5).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that not all neutrophils in the oral cavity display similar levels of cell surface CD marker expression (5,11,12). In the healthy oral cavity, neutrophils are in a parainflammatory state, whereas in a diseased cavity, neutrophil phenotypes are changed to a proinflammatory state, with neutrophils in the parain-flammatory and proinflammatory states expressing low levels and high levels of CD markers, respectively (5).…”
Section: Resultsmentioning
confidence: 99%
“…Images of Western blot and nuclear euchromatin fraction were analyzed by Image J (National Institutes of Health, Bethesda, MD, USA) according to a previous study. 22 The number of neutrophil fluorescent spots were counted using Image-Pro Plus 6.0 (Media Cybernetics, Inc., Rockville, MD, USA). Statistical analysis and charting were performed with GraphPad Prism 5 (GraphPad Software, San Diego, CA, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Circulatory neutrophils, on the other hand, were shown to be activated during gingivitis onset as shown by the markers CD55, CD63, CD11b, and CD66a. Also in 2018, this group further characterized the morphology of the para-inflammatory health-associated phenotype described in 2016, and compared it to the naïve morphology of blood neutrophils as well as to the pro-inflammatory phenotype of oral neutrophils in periodontitis (58). They revealed that pro-inflammatory neutrophils in periodontitis showed less granulation, lighter cytoplasms and higher amounts of nuclear euchromatin, as assessed by electron microscopy, compared to the para-inflammatory oral health neutrophils.…”
Section: Possible Neutrophil Subsets In Periodontal Health and Inflammentioning
confidence: 99%